Toxicity assessment of arsenic and cobalt in the presence of aquatic humic substances of different molecular sizes - Watanabe, Claudia Hitomi [UNESP]; Costa Monteiro, Adnivia Santos [UNESP]; Jeunon Gontijo, Erik Sartori [UNESP]; Lira, Vivian Silva [UNESP]; Bueno, Carolina de Castro [UNESP]; Kumar, Nirmal Tej [UNESP]; Fracacio, Renata [UNESP]; Rosa, Andre Henrique [UNESP] (Elsevier B.V., 2017)
using environmentally relevant concentrations of arsenic and cobalt were conducted both in the presence and absence of aquatic humic substances (AHS) and the fractions of different molecular sizes in the range of (< 5, 5-10;10-30; 30-100 and > 100kDa) using the microcrustacean Ceriodaphnia dubia. AHS together with arsenic reduced the toxicity, and the toxicity decreased in fractions of larger molecular size AHS. Despite the presence of cobalt, the reduction in toxicity was not observed and that depended on the molecular size of AHS. There was a trend of enhanced toxicity for Co in fractions of larger molecular sizes, opposed to that found for arsenic. Thus, the humic substances alter toxicity of trace elements, and this effect varies depending on the size of the humic substances
Keywords: Humic substances; Toxicity; Arsenic; Cobalt; C. dubia; Molecular size